Evaluation of Anticancer and Neuroprotective Properties of Curcumin: a Network Analysis - Mohammad Rostami-Nejad; Mohammadreza Razzaghi; Somayeh Esmaeili; Alireza Zali; Majid Rezaei-Tavirani; Mohammah Hossein Heidari; Mostafa Rezaei-Tavirani; Mona Zamanian-Azodi*; Nayebali Ahmadi (Iranian Society of Pharmacognosy, 2020)
Background and objectives: Curcumin as a medicinal substance has shown effective in different kinds of diseases especially cancer. To understand its underlying mechanism, molecular complementary study of differentially expressed microRNAs (DEMs) could assist. In this view, regulatory network analysis of DEMs of melanoma cancer treated with curcumin versus the untreated male Mus musculus was investigated in this study. Methods: Data was obtained from the database of Gene Expression Omnibus (GEO), https://www.ncbi.nlm.nih.gov/geo/.At first, the log fold change (FC)≥ 2 was assigned for predicting a cut off for DEMs in the following study. GEO2R detected a number of 250 top significantly changed microRNAs based on the priority of the most statistically significant ones. These miRNAs were then explored for regulatory network analysis via Cytoscape softwarev.3.7.2 and its plug-ins. Results: The findings indicated that a number of 21 miRNAs were statistically significant with differential expression amounts. Regulatory network also identified important microRNAs of mmu-miR-199a, mmu-miR-199b, mmu-miR-21, mmu-miR-142-3p, mmu-miR-148a, mmu-miR-214 and genes of Pkp3, Usp19, Ercc4, Ttc25, Atp13a2, Akr1b7, Umod, Nup188, Imp3, and Tmem74b. The highest ranked hub was mmu-miR-199a, which had nine connections. Conclusion: The present study offers new insights into the molecular mechanism of curcumin health benefits in melanoma cancer.